Magnetoviscous effects in ferrofluids - Odenbach Stefan (Berlin Springer-Verlag, 2002)
Suspensions of magnetic nanoparticles or ferrofluids can be effectively controlled by magnetic fields, which opens up a fascinating field for basic research into fluid dynamics as well as a host of applications in engineering and medicine. The introducto
Keywords: Ferrofluids; Magnetohydrodynamics